Impact of access to childhood health services on healthy life expectancy of the older population - Liu, Chen; Hou, Xiaochun; Wang, Qiong; Xu, Xinrui; Wu, Bingyi; Liu, Jun (Frontiers in Public Health, 2023)
Background Life course theory provides new perspectives on the impact of early experiences on health in old age, where unfortunate childhood experiences can alter an individual's health trajectory. This study aims to calculate the healthy life expectancy of the older population in China under different childhood experiences, and to explore the influence of childhood medical and health services on the health level of older adults. Methods Differences in healthy life expectancy of the older population under different childhood experiences were analyzed using the multi-state life table method to calculate the healthy life expectancy by sex and place of birth, based on the cohort data of Chinese Longitudinal Healthy Longevity Survey (CLHLS) from 2008 to 2018. Results The probability of the transition risk from health to non-health gradually increased with age, while the probability of the transition risk from non-health to health decreased with age; In both urban and rural areas, on the probability of the transition risk from health to non-health, the older adults who were able to receive timely medical and health services in childhood were lower than those who failed to receive medical services in time (Z = −5.833, P < 0.05), but the probability of the transition risk from non-health to health was the opposite (Z = −5.334, P < 0.05); The probability of the transition risk from health to death is also higher in older adults who were unable to receive timely medical care in childhood (Z = −5.88, P < 0.05); The healthy life expectancy and its proportion in the remaining life expectancy of older people who received medical and health services in time during childhood were significantly higher than those of their peers (Z = −5.88, P < 0.05). Conclusions The lack of medical services in childhood has a negative effect on the health of older adults. The healthy life expectancy and its proportion of remaining life expectancy were higher for rural older adults than for urban older adults under the same health care conditions in childhood; the health benefits of good access to health care environment or conditions in childhood were greater for rural older females.